Nanofabrication of 2D photonic crystals for PCSELs emitting in UV region - Sunil, Vismaya (My University, 2024)
Lasers are light sources that produce coherent beams. Semiconductor lasers offer notable advantages such as compact size, lower power consumption, and extended lifespan over other laser types. Among different semiconductor lasers, photonic crystal surface-emitting lasers (PCSELs) are recognized for their high optical output power and low beam divergence, achieved through the use of a two-dimensional photonic crystal. The proposed PCSELs use photonic crystals which offer refractive index contrast in two dimensions. This creates a standing wave with zero group velocity and vertical emission through Bragg diffraction. PCSELs have been successfully demonstrated in the visible and infrared wavelengths, but not yet in the ultraviolet (UV) range. This gap represents a significant opportunity, as UV-emitting PCSELs find potential applications in lithography, sterilization, and processing of materials. This project aims to explore different etching techniques to deep into the cladding layer of the PCSELs. To keep the optical losses low, the vertical field profile should not overlap with the absorbing metal layer used for the p-contact. Therefore the distance between this metal and the QWs needs to be large and on the order of 300-400 nm. The bottom of the photonic crystal holes on the other hand should be very close to the top QW (about 60 nm). To fulfill both these requirements the photonic crystal should have an etch depth of about 300 nm. Etching is preferred over alternative methods, such as over-growth or mass transport, due to its presumed simplicity and cost-effectiveness.
Keywords: Photonic crystal, Etching, ICP-RIE, UV Lasers, AlGaN, PCSEL